(untitled) (Eurasian Journal of Engineering and Technology, 2023)
The task of evaluating and diagnosing the current condition of the transformer is set in the article. When assessing the current situation, it is necessary to know where the defects are localized and the reasons for their appearance. Therefore, classification of causes and types of transformer damage was considered and analyzed